Lignin conversion using catalytic ionic liquids: understanding the role of cations, anions, and hammett acidity functions - Singh, Sandip K.; Dhepe, Paresh L. (Industrial & Engineering Chemistry Research, 2019)
Because it is undisputable that lignin depolymerization is a must to make the biorefinery concept economically feasible, several efforts are put toward it; however, a lot of catalyst designing is required to achieve efficient depolymerization activities. In this work, we show a systematic approach in the synthesis and characterization of ionic liquids (ILs) with varying combinations of cations (imidazole, benzimidazole, phosphonium, and ammonium) and anions (HSO4, PTS (p-toluenesulfonate), Cl, H2PO4, SnCl3, FeCl4, and CuCl3) for the depolymerization of lignin into low-molecular weight aromatic fractions (<220 g/mol) under mild reaction conditions (120 degrees C, 1 h, ambient pressure). In a methodical approach, effects of various reaction parameters such as temperature (70-170 degrees C), time (15-360 min), pressure (N-2, 0.5-3 MPa), solvents and substrate, and so forth were studied to achieve best activity. Among all the catalysts, IL with the imidazolium cation and HSO4 as the anion showed best activity (78% yield). Subsequent to depolymerization, three aromatic monomers (5 wt % pure vanillin) were isolated using flash column chromatography. These aromatic monomers were characterized using gas chromatography (GC), GC-mass spectrometry, and NMR techniques for their purity. Hammett acidity functions (H-0) of ILs were measured using UV-vis photo-spectroscopy, and values are correlated with lignin depolymerization results. Lignin and tetrahydrofuran-soluble products were thoroughly characterized using assorted physicochemical techniques such as NMR (H-1 and C-13), gel permittivity chromatography, thermogravimetric analysis, and so forth. The catalyst was recycled up to six runs and showed similar results in consecutive reactions.

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw